Pengaruh Pemberian Konsentrasi Biochar Kayu Meranti Sebagai Media Tanam Terhadap Pertumbuhan Tanaman Tomat (Solanum lycopersicum L.) - Normila Santi; Maya Istyadji; Rizky Febriyani Putri (GLOBAL SCIENTS PUBLISHER, 2026)
Tomato (Solanum lycopersicum L.) productivity is influenced by the quality of the growing medium. Meranti wood biochar has the potential to improve soil properties and support plant growth. This study aimed to analyze the effect of different concentrations of meranti wood biochar on tomato biomass based on plant dry weight and to determine the most effective concentration. The study employed a Completely Randomized Design (CRD) with one factor consisting of five treatments: (100% soil), (5% biochar + 95% soil), (10% biochar + 90% soil), (15% biochar + 85% soil), and (20% biochar + 80% soil), with five replications for each treatment. Data were analyzed using normality and homogeneity tests, followed by one-way ANOVA and Duncan's Multiple Range Test (DMRT) at a 5% significance level. The results showed that meranti wood biochar significantly affected tomato biomass (p = 0.003). The treatment produced the highest dry weight (79.0 g), indicating that the application of 10% meranti wood biochar was the most effective concentration for increasing tomato biomass.